Hadis tentang Kebebasan Budak: Studi Historis terhadap Akar Emansipasi Sosial dalam Islam - Ahmad Mutawalli Nasution (Arba: Jurnal Studi Keislaman, 2025)
Slavery is a deeply rooted social practice in pre-Islamic society and persisted in the early Islamic period, raising serious issues related to justice and equality. In this context, Islam presented fundamental changes through the Prophet’s teachings, as recorded in hadiths, that emphasize not only legal aspects but also moral and social dimensions, leading to emancipation. This study aims to examine the historical role of hadith in forming the foundation of slave liberation as the root of the Islamic social emancipation movement and its contribution to contemporary humanitarian values. The method employed is a qualitative historical-hermeneutic approach, utilizing content analysis of ṣaḥīḥ hadiths from various primary books, including Ṣaḥīḥ al-Bukhārī, Ṣaḥīḥ Muslim, and Sunan Abī Dāwud, with the selection criteria of hadiths that explicitly regulate, motivate, or sanction the liberation of slaves. The research findings show that these hadiths do not merely contain normative commands but also serve as moral instruments to eliminate discrimination, elevate the dignity of slaves as equal human beings, and guide society toward a more just social transformation. For example, hadiths on the virtue of freeing slaves as an expiation for sins, the validity of certain religious practices, and alternatives to corporal punishment reflect a gradual strategy toward the abolition of slavery. In conclusion, the Prophet’s hadiths lay the foundation for social emancipation, emphasizing the values of justice, humanity, and equality that remain relevant in addressing modern issues of inequality.